Pengaruh Teknologi Dalam Peningkatan Kemampuan Bahasa Indonesia Di Era Digital - Arrafi Bagus Pratama; Juan Danny Saputra; Arif Marzuki; Muhammad Rafli Nurfiansyah; Rizki Yoga Pratama; Dewi Puspa Arum (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to determine the role of educational technology in changing the landscape of Indonesian language education in the digital era. The methodology used includes a literature review to identify recent developments in the use of educational technology in language teaching. The results of this research show that educational technology has contributed significantly to improving the quality and efficiency of learning, facilitating distance learning through platforms such as Zoom and Google Meet, and encouraging innovation in educational strategies. This study shows that the role of educational technology does not only focus on technical aspects, but also influences the learning paradigm by changing the perspective on the role of teachers and students. However, the use of educational technology also presents challenges, including accessibility and socio- psychological impacts on students. Therefore, sophisticated strategies are needed to effectively incorporate educational technology into the language teaching curriculum. This study provides insight into how educational technology influences the transformation of Indonesian language education in the digital era. The methods and results of this research provide a better understanding of the complex role of educational technology in shaping education that is more adaptive and relevant to current developments.